Optimización de la producción de hipoclorito de sodio generado a partir de electrolisis. (2024)
This study evaluated the production of sodium hypochlorite through electrolysis in an electrolytic cell designed and built on a laboratory scale, with a capacity of 1,425 L and 200 grams of salt. The purpose of this study was to evaluate the incidence of variables such as flow, 3 different voltages (3V, 4V and 4.5V) and the distance between the electrodes that were taken (2mm, 4mm, 6mm, 8mm) and the time The operating time for each assembly was 120 minutes, performing an analysis every 30 minutes.